How Community – Oriented Medicine is Implemented in Medical Education - Werdhani, Retno Asti; Kusuma Dewi, Dian; Findyartini, Ardi; Ramlan, Andi Ade; Sugiharto, Agus (Journal of Community Medicine and Public Health Research, 2024)
The Community Oriented Medical Education (COME) approach to medical education focuses on the population and individuals while covering all elements of health problem priorities. The World Health Organization (W.H.O) Strategic Framework identifies five key strategic directions for enhancing basic medical education to meet existing health concerns. A long-term, integrated module across disciplines is one strategy that the Faculty of Medicine at Universitas Indonesia has experienced in its implementation in both community and clinical medicine. The module includes a variety of field practices (hospital and primary care) as well as inter-departmental personnel (committees and tutors). The module has bridged the gap between community medicine and clinical medicine, with integrated staff as well as collaboration between the departments of community medicine and clinical medicine. Community medicine has been seen as important not only for epidemiological concerns but also as part of the clinical teaching approach that prepares students for careers in hospitals or primary care after graduation. COME can be taught in multidisciplinary or inter-departmental collaboration to accomplish applied learning outcomes for individuals and community health activities. COME ensures our education system produces medical graduates to meet health system needs with the help of faculties and teachers who are also responsible for community health and well-being.